ACCURACY OF 3D-PRINTED SURGICAL GUIDES IN DENTAL IMPLANTOLOGY: A NARRATIVE REVIEW OF STATIC, DYNAMIC, AND ROBOTIC TECHNIQUES - Paweł Buć; Jagoda Józefczyk; Karolina Buć; Łukasz Krzystek; Konrad Zieliński; Karolina Ganczar; Michał Mazurek; Marianna Rudzińska; Mikołaj Zalewski; Stanisław Jurkowski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Digital technologies and 3D printing have transformed implant dentistry, enabling improved precision in implant placement through static and dynamic computer-assisted approaches. Ensuring accurate implant positioning is essential for long-term success, particularly in anatomically demanding or esthetic regions. Objective: To evaluate the accuracy of 3D-printed surgical guides and compare their performance with dynamic navigation, robotic systems, and freehand implant placement techniques. Materials and Methods: A structured narrative review was conducted using the PubMed database (up to November 2025). A total of 44 records were identified, of which 19 studies met the inclusion criteria. These comprised randomized clinical trials, prospective and retrospective studies, in vitro investigations, and systematic or narrative reviews. Data extraction focused on linear and angular deviations, clinical outcomes, guide design, printing technology, and planning protocols. Results: Across included studies, 3D-printed guides consistently demonstrated high accuracy, with mean platform deviations of approximately 0.2–1 mm, apical deviations of 0.5–1.6 mm, and angular deviations of 1–3°. Clinical findings mirrored in vitro results. Dynamic navigation achieved comparable accuracy, while robotic systems showed even lower angular deviations (<1.6°). Guide stability, printing technology, and imaging protocol significantly influenced outcomes. Conclusion: 3D-printed surgical guides provide predictable, clinically acceptable precision and enhance the safety and efficiency of implant placement. Dynamic and robotic systems offer promising complementary technologies. Further long-term clinical trials are needed to establish their definitive clinical impact.